EFFECTIVENESS OF MALEIZATION OF TILAPIA (Oreochromis niloticus) SEEDS BY SOAKING IN COCONUT WATER - Fathin Maulana Putra Wardana; Azam Bachur Zaidy; Suratman Suratman; Nayu Nurmalia; M. Harja Supena (Universitas Mataram, 2026)
Market demand, especially the export market, requires tilapia with an average weight of more than 500 g. To achieve a size of 500 g, farmers experience obstacles requiring a long time, especially because the growth of female tilapia is slower than male tilapia. The purpose of this study was to produce a higher ratio of male tilapia seeds. The research design was a completely randomized design with 2 treatments and three replications. The treatment tested was soaking tilapia seeds with 40% coconut water compared to the control. Parameters measured included male sex ratio, survival, biomass and feed conversion. The results showed that coconut water soaking significantly increased the male sex ratio to 71.8% compared to the control of 56.7%. The average weight of fish soaked in coconut water was higher with a significant difference of 7.17 g compared to 3.17 and biomass of 1,100 g compared to 571 g. The feed conversion of treated fish was lower and a significant difference of 1.5 compared to the control of 2.9. The research results can be used by fish breeders to produce high-quality fry with good production performance and efficiency in artificial use.